Application of intermediaries motivation in the distribution channels of car market - Савич, Олександр Петрович (Technology audit and production reserves, 2017)
The object of research is the policy of motivation and training. Practice shows that the main problem of automakers today is motivation of intermediaries in the distribution channels and qualifications of their staff, i. e. staff training. This applies particularly to car dealers, as revenue from car sales fall every year and profitability of car sales too low, sometimes only 3 % of the sale price of the car, so it is important to further motivate all intermediaries in the distribution channels in the chain of distribution by automaker. Equally important in the activity of automakers and dealer network is a system of education and training for the automotive industry due to the fact that consumers trust more direct contact with the seller and less – advertising. The method of research is the general scientific methods such as systems analysis, synthesis, induction, deduction, abstraction and special scientific methods, including methods of sociological research and comparison. Materials are theoretical research of scientists, statistics and practical knowledge and experience of the author in the car market of Ukraine. The obtained results allow automakers to introduce an effective motivational system for sales of car and spare parts, as well as providing quality service. But it should be noted that any motivation will work provided the combination of material and non-material incentives. Equally important in the activity of automakers and dealer network is an effective system of education, training and retraining for the automotive industry. We propose to organize education and training of specialists using two-level training matrix, which includes the system of training young professionals and staff training system.